Automated red cell exchange in sickle cell disease patients: Retrospective analysis of series of cases in a tertiary care hospital in Eastern India - Girijanandini Kanungo; Priyanka Nagrath; Priyanka Samal; Santosh Mishra (Asian Journal of Transfusion Science)
Red cell exchange is important to treat acutely ill sickle cell patients, but it is time-consuming. An automated red cell exchange technique using cell separators developed by different manufacturers helps in removal of sickled hemoglobin and improving blood viscosity. The use of these cell separators permits automated red cell exchange to be performed safely and smoothly with the isovolemic hemodilution. The retrospective analysis of seven cases for automated red cell exchange was performed in IMS and SUM Hospital from September, 2019 to July 2021. One procedure was performed on COBE Spectra Apheresis System and the rest six using Spectra Optia Apheresis System. These procedures were performed on the patients and the decision to perform these procedures was based on clinical indications for red cell exchange following the ASFA guidelines 2019. After only one procedure, all the patients have their sickle hemoglobin reduced to a safe level. End hematocrit was observed to be 33% in three cases, 31.9% in one case, and 30% in the rest three. A total number of red blood cells (RBCs) transfusion in all the cases were 7, 6, 8, 5, 6, 7, and 7 with an average hematocrit of 55%, 56%, 54%, 56%, 55%, 51.7%, and 52.2%, respectively. All the patients partially phenotypically matched, leukoreduced, gamma-irradiated, fresh packed RBCs were provided. Automated red cell exchange came out to be successful in reducing the symptoms along with the improvement in laboratory parameters. New-generation automated apheresis equipment like Spectra Optia, the case series provides better monitoring and also reduces apheresis-related complications.